To Tend or to Subdue? Technology, Artificial Intelligence, and the Catholic Ecotheological Tradition - Labrecque, Cory Andrew (Religions, 2022)
In February 2020, the president of Microsoft, the executive vice president of IBM, the director general of the Food and Agriculture Organization (FAO) of the United Nations, and the former Italian Minister of Innovation joined the president of the Vatican’s Pontifical Academy for Life in Rome to sign The Rome Call for AI Ethics. In doing so, they promoted a shared sense of responsibility and commitment—by industry, government, and Church—to uphold certain ethical standards in the areas of digital innovation, artificial intelligence, and technological progress. In this article, I discuss The Rome Call for AI Ethics in conjunction with Pope Francis’ rendering of integral ecology and the technocratic paradigm in Laudato Si’. My aim here is to link Catholic teaching on technology (using AI as a starting point) to the environment and the ecological crisis.